Strategi Pelayanan Terpadu Satu Pintu dalam Meningkatkan Layanan Adminitrasi di Kemanag Kota Malang - Multazam, Firsta Nurud Dhuha; Ningsih, Nerizza Nur Rossi; Wicaksono, Muhammad Rowi Bagus; Walid, Muhammad (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to analyze in depth the service strategies implemented by the PTSP Ministry of Religion of Malang City in an effort to improve the quality of administrative services for the community. This research uses a qualitative approach with data collection methods that include interviews, observations and documentation studies to obtain a comprehensive picture of the PTSP strategy planning and implementation process. The research results show that careful strategic planning and implementation of the SENYUM application in PTSP services is able to increase the efficiency and effectiveness of administering administrative services, as well as providing easy access for the wider community. These findings indicate that optimizing technology and public service innovation can encourage improvements in service quality in the government sector. This research also provides a number of strategic recommendations for further development in the implementation of PTSP, especially in government agencies, so that they are more responsive to community needs. In addition, this research proposes several directions for future research in order to improve the findings and provide broader contributions in the context of improving public services in the future.